Adopting Technology Environment Organization Framework in Virtual Learning through Cloud Computing of Higher Education Institution - Menta, Amanda Jane C. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – This study intends to adopt the Technology Environment Organization framework in virtual learning through cloud computing in a higher education institution that will streamline the operation of education. Method – A systematic review using descriptive research was presented highlighting the model of the TEO framework in adopting cloud-based computing implementation in the educational system of the HEIs. The study features the critical success factor affecting cloud computing implementation which can be a key point as guidelines and step to embrace technological advancement in the field of education in the Philippines. Results – The study is appeared to contribute to the organization of higher education institutions in the Philippines to make informed decisions relevant to the advancement of cloud technology service selection and deployment processes. The migration of cloud computing implementation in developing countries is proven successful in achieving the benefits of reducing IT cost, scalability, business continuity, collaboration efficiency, easy management and access, complexity, and compatibility. Thus, the Philippines is admissible to a strategic implementation to widen and improve adopting cloud services. Conclusion – Adoption of cloud computing in higher education institutions is an alternative solution in streamlining and managing the educational system infrastructure. Recommendation – Considering the critical success factor affecting cloud computing implementation the TEO framework is a strategic approach to embrace technological advancement in the Philippines. Practical Implication – The use of cloud computing in the virtual learning of the HEIs has been proven effective in the educational operation considering the critical success factor with the Technology Environment and Organization methods. This aligns with new educational system development in improving the infrastructure of the learning platform of the HEIs into more advance and accessible features of the learning delivery through its stakeholders.